ANALISIS KELENGKAPAN FORMULIR INFORMED CONSENT PADA KASUS BEDAH UMUM GUNA MENUNJANG KUALITAS PELAYANAN DI RS BHAYANGKARA TK.II SARTIKA ASIH BANDUNG - Pujilestari, Intan; Nabila, Sri; Monica, Rizqi Dimas; Hada, Encep; Rohaeni, Neni (Jurnal TEDC, 2024)
Health is a very important basic need for everyone. The results of the preliminary study carried out, took a sample of 10 files of informed consent forms from general surgery patients in January. Of the 10 files, there were 7 incomplete informed consent forms (70%). This study aims to determine the completeness of the informed consent form in general surgery cases to support service quality. The research method used is a descriptive method with a quantitative approach. The population in this study was the informed consent form for surgical operations in November-January 2023, namely 351. The samples taken from the population were 78 samples. The sampling technique is incidental sampling. The data collection techniques used were observation, interviews and documentation. The results of the research carried out show that of the 78 samples of informed consent sheets in November-January 2023, namely for completeness in filling out informed consent on patient identification variables, 77 files (98%). Important reporting variables amounted to 64 files (43%). The authentication and identification variables of the person in charge amounted to 66 files (85%). Meanwhile, the good and correct recording variable was 76 files (98%). The completeness results of filling out the informed consent form in the patient's medical record file for surgical operations in November-January 2023 are not 100% complete